Highways for ions in polymers - 3D–imaging of electrochemical interphase formation. (10th July 2015) - Wesp, Veronika; Zakel, Julia; Schäfer, Martin; Paulus, Ilka; Greiner, Andreas; Weitzel, Karl-Michael
Graphical abstract: Abstract: The formation of a cesium interphase in-between a polymer film and a platinum electrode has been initiated by low energy bombardment induced ion transport. To this end two different samples of a poly(p-xylylene)(PPX) film, deposited on a platinum electrode have been bombarded by a low energy cesium ion beam. Ions are transported through the film according to the laws of electro-diffusion. They are neutralized at the interface between the PPX film and the metal electrode. Consequently, a cesium interphase is formed. 3D imaging of the interphase by means of time-of-flight secondary ion mass spectrometry (ToF-SIMS) reveals a correlation between structural characteristics of the interphase and conduction properties of the PPX film. The bombardment of PPX films consisting of a homogenous network leads to the formation of a uniform interphase. The bombardment of PPX films with non-intermittent pathways (NIPs) for the transport of ions leads to the formation of cesium islands which ultimately spread out laterally leading to a non-uniform interphase behind the PPX film. This picture is supported by measurements of the ionic conductivity which differs characteristically for the two kinds of PPX films.